Role of antigen presentation in the production of pro-inflammatory cytokines in obese adipose tissue. (June 2016) - Majdoubi, Abdelilah; Kishta, Osama A.; Thibodeau, Jacques
Highlights: The adaptive arm of the immune system contributes to inflammation in adipose tissues during diet-induced obesity. The number of activated T cells increase in adipose tissue with inflammation. MHC molecules play a key role in the activation of T cells and the generation of T regulatory cells. Cytokines modulate the expression of MHC molecules on adipocytes and cells of the stromal vascular fraction. Abstract: Type II diabetes regroups different physiological anomalies that ultimately lead to low-grade chronic inflammation, insulin resistance and loss of pancreatic β-cells. Obesity is one of the best examples of such a condition that can develop into Metabolic Syndrome, causing serious health problems of great socio-economic consequences. The pathological outcome of obesity has a genetic basis and depends on the delicate balance between pro- and anti-inflammatory effectors of the immune system. The causal link between obesity and inflammation is well established. While innate immunity plays a key role in the development of a pro-inflammatory state in obese adipose tissues, it has now become clear that adaptive immune cells are also involved and participate in the cascade of events that lead to metabolic perturbations. The efficacy of some immunotherapeutic protocols in reducing the symptoms of obesity-driven metabolic syndrome in mice implicated all arms of the immune response. Recently, the production of pathogenic immunoglobulins and pro-inflammatory cytokines by B and T lymphocytes suggested an auto-immune basis for the establishment of a non-healthy obese state. Understanding the cellular landscape of obese adipose tissues and how immune cells sustain chronic inflammation holds the key to the development of targeted therapies. In this review, we emphasize the role of antigen-presenting cells and MHC molecules in obese adipose tissue and the general contribution of the adaptive arm of the immune system in inflammation-induced insulin resistance.